Tumor de Leydig simulando una neoplasia germinal - Gamboa Acuña, Brenda Adriana (2016)
Main findings A case is presented of a Leydig cell neoplasm in a 25 year-old male patient with no classic risk factors with an atypical outcome. The tumour mass was histologically analysed and was found to have features compatible with a germ cell neoplasm. A right orchiectomy was performed, followed by chemotherapy. After treatment, pulmonary metastasis, lymph nodes, and peri-hepatic hydronephrosis were found. The patient died two months after his last hospital admission. Case hypothesis Leydig cell tumours account for 1% to 3% of all testicular tumours. They occur at any age, especially in children, and between the third and sixth decade of life. Around 90% are benign, and 10% are malignant; these latter usually occurring between 50 and 60 years old, and are associated with sizes larger than 5 cm and gynecomastia. Finally, it is difficult to predict the development of the disease based on histopathological observations. Promising future implications Although non-germ cell tumours are rare, it is important to consider them in the differential diagnosis of testicular tumours, particularly in those of non-seminoma origin. Immunohistochemistry is useful for the differentiation of testicular tumours in those cases when conventional histology shows no conclusive findings.